Arab Society Customs in School Found Within Kitab Al Arabiyyah Baina Yadaik - Ritonga, Nur’ainun; Sahyoni, Sahyoni; Nurbayan, Yayan; Burdah, Ibnu; Rahman, Nur Fuadi (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Language and culture are closely intertwined and inseparable. When someone learns a language, they also acquire the values and norms of the community that speaks it. In Arabic language teaching books like Arabiyyah Baina Yadaik, various materials introduce aspects of Arab culture such as social life, education, health, economy, and the environment. The purpose of this study is to investigate the institutional and non-institutional customs within the Arab community in schools as presented in the book